2009
DOI: 10.1523/jneurosci.2351-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine and Paracrine Roles for ATP and Serotonin in Mouse Taste Buds

Abstract: Receptor (type II)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
174
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(183 citation statements)
references
References 42 publications
5
174
2
2
Order By: Relevance
“…Consistently, taste cells of the type II have been demonstrated to release ATP into intercellular space upon gustatory and electrical stimulation (Huang et al, 2007;Romanov et al, 2007). This entails activation of P2X2/P2X3 receptors on afferent taste nerves (Bo et al, 1999;Kataoka et al, 2006) and a variety of P2X and P2Y receptors on taste cells (Baryshnikov et al, 2003;Kataoka et al, 2004;Bystrova et al, 2006;Huang et al, 2009;Huang et al, 2011). Taste cells of the type II lack conventional synapses (Royer and Kinnamon, 1991;Tabata et al, 1995), but instead release ATP via voltage-gated channels (Huang et al, 2007;Huang et al, 2011;Romanov et al, 2007;Romanov et al, 2008).…”
Section: Introductionmentioning
confidence: 94%
“…Consistently, taste cells of the type II have been demonstrated to release ATP into intercellular space upon gustatory and electrical stimulation (Huang et al, 2007;Romanov et al, 2007). This entails activation of P2X2/P2X3 receptors on afferent taste nerves (Bo et al, 1999;Kataoka et al, 2006) and a variety of P2X and P2Y receptors on taste cells (Baryshnikov et al, 2003;Kataoka et al, 2004;Bystrova et al, 2006;Huang et al, 2009;Huang et al, 2011). Taste cells of the type II lack conventional synapses (Royer and Kinnamon, 1991;Tabata et al, 1995), but instead release ATP via voltage-gated channels (Huang et al, 2007;Huang et al, 2011;Romanov et al, 2007;Romanov et al, 2008).…”
Section: Introductionmentioning
confidence: 94%
“…However, no studies have yet resolved whether the salty and sour responses observed in type III taste cells arise from two distinct populations of cells or whether receptors for sour and salty taste are coexpressed in the same type III cells. Much of the difficulty in resolving this question arises from the prevalence of cell-to-cell communication in the intact taste bud, which makes it difficult to determine whether the response of a taste cell to a tastant is attributable to the tastant interacting with receptors/channels expressed by the cell itself or whether the cell is being activated indirectly through cell-to-cell communication (Caicedo et al, 2002;Tomchik et al, 2007;Huang et al, 2009;Roper, 2013). This difficulty is of particular concern for type III taste cells, which commonly respond to multiple taste qualities, including sweet, bitter, and umami (Tomchik et al, 2007), de- Ca 2ϩ responses to taste stimuli and KCl depolarization in isolated CV taste cells can be used to reliably identify AI salt-responsive type III taste cells.…”
Section: B)mentioning
confidence: 99%
“…43 Upon secretion, ATP acts as a neurotransmitter on nearby sensory afferent fibers 44,45 ; ATP also acts as a paracrine/autocrine hormone, binding with receptors expressed on neighboring taste receptor cells. [46][47][48][49][50] Type III cells release serotonin, c-amino butyric acid, and norepinephrine and are most notable for possessing synapses. [51][52][53][54] These cells, also termed presynaptic cells, express voltage-gated calcium channels associated with neurotransmitter release, enzymes for serotonin, and c-amino butyric acid, as well as uptake transporters for biogenic amines.…”
Section: Taste Bud Anatomy and Physiologymentioning
confidence: 99%